Historical legacy in ethno-religious affiliation in Malaysia: a comparative study between the Peninsula and Sabah - A Rahman Tang Abdullah (Penerbit UMS, 2020)
This paper discusses the historical dimension that reflects the circumstances and differences which shape the relations between ethnicity with religious affiliations in Peninsular Malaysia and Sabah. The basis for the discussion is derived from the current reflection on multi-ethnicity and multi-religious society in Malaysia which is not merely based on a single context at national level. In fact, it is evident that these two interrelated aspects are actually subjected to different contexts in the sub-regions; namely West Malaysia (also known as the Peninsula) and East Malaysia which is composed of Sabah and Sarawak. The different status-quo also reflects different impacts on all issues related to ethnicity and religious sentiments in Malaysia as a whole. Without ignoring the focus on the current perspectives on the differences in ethnicity and religion between the Peninsula and Sabah, it is important to explore the historical development during the colonial period which shaped the phenomena in ethnicity and religion in both areas.